Siri' Na Pacce Culture in Judge's Decision (Study in Gowa, South Sulawesi Province) - Muhammad Ikram Nur Fuady (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
Manimbohoi Village in Gowa District is part of the Makassar tribe who still hold the Siri' na Pacce culture that highly upholds shame, honour, dignity, and togetherness as Adat Law. During this time, there is often a difference between the Traditional Law of Siri' Na Pacce and Indonesian Positive Law in upholding the material values of criminal acts, so that judges' decisions are difficult to accept by local communities. This study aims to determine the influence of the culture of Siri na Pacce' regarding the judge's decision in constructing the criminal offences committed by residents of Manimbohoi with the decision Number: 66/Pid.B/2012/PN.Sungg.This study used a normative empirical approach with a descriptive-qualitative method that analyses cases of judges' positions and judgments on decisions plus data obtained by interviews with the Adat Officer, Manimbohoi’s people, the judge in Sungguminasa District Court.The results of the study showed that 1)The Siri' Na Pacce as unwritten laws and positive Indonesian law as written laws have the same position in the Republic of Indonesia which can be carried out as long as there is no comparison in the KUHP as Criminal Code; 2)In the decision, the judge has been progressive by imposing a sanction lower than the prosecutor's request indicating that the judge acknowledges Siri 'na Pacce even though it does not include it in writing on the consideration of the points of judges; 3)The weight and lightly of punishments and values of Siri' na Pacce's held by the judge depends on the benefits and feelings held by the judge as a benchmark based on the individual judge's personality; 4)The judge acknowledges the culture of Siri 'Na Pacce as living law but has not been able to put it into judgment as justification, forgiveness, and mitigation reason; 5)Therefore, this Siri' Na Pacce should be maintained Indonesian identity.